TOXICITY ASSESSMENT OF TEXTILE DYES VIA OXIDATIVE STRESS HYPOTHESIS FOR IRAQI TEXTILE WORKERS - LAMIA A. M. AL-MASHHEDY (International Journal of Pharma and Bio Sciences, 2013)
Textile dyes are the most important environment-polluting agents and particularly working environment, so the workers are vulnerable to many diseases, especially cancer, such as skin and lung cancer. Many of the workers are occupation exposed to dye, but little is known for their risk and chemical influence of the dyes on their health, for that the present study was taken up to assess the azo dyes toxicity, risk and knowledge about the health hazard of these dyes by determination of oxidant and antioxidant status of Iraqi textile workers in Hilla city. The mean age of 45 textile workers was 37±5.2 years compared with 40 person working in an office business aged 35±2.5 years. When enquired about whether dyes to affect body organ(s), all the workers agreed that dye(s) will affect skin, but they are not aware that dyes could affect other parts of the body for that, the present study included evaluation of lipid peroxidation via determining of the main end product malondialdehyde (MDA) as an oxidant and Vitamin E and reduced glutathione(GSH) , superoxide dismutase (SOD), catalase(CAT), as an antioxidant as well as assessment of Lipid profile(cholesterol, triglyceride TG ,high-density lipoprotein HDL, low-density lipoprotein LDL and very low-density lipoprotein vLDL) beside the evaluation of liver enzyme activity (AST and ALT) rather than determination of thyroid hormone T4 and T3 in an attempt to estimate the effects of dyes on various tissues inside the body.